MEMAHAMI STRATEGI IMPLEMENTASI SISTEM PENGENDALIAN MANAJEMEN KOMPREHENSIF - Fransiskus E. Daromes; Suwandi Ng; Kunradus Kampo (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2018)
A management control system is a mechanism that ensures, encourages, enables, or sometimes "forces" people within an organization to do what is best for the organization. This research elaborates a comprehensive management control system based on literature review and case studies at Aston Makassar Hotel & Convention Center and Grand Clarion Hotel & Convention Makassar. The results show that although in different ways and mechanisms, these hotels have comprehensive management control system mechanisms that are used to ensure and drive the achievement of corporate objectives. The initial consideration of the entire set of management control systems in hotels is the cultural control that is reflected in the vision-mission, core values, organizational culture and uniqueness of the company that is a form of joint management control. In addition, these potentials and values ​​need to be comprehensively understood and implemented with other control mechanisms so that these hotels can achieve their vision and mission.